2013
DOI: 10.1016/j.ajpath.2012.10.018
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Drug Tamoxifen Counteracts the Pathology in a Mouse Model of Duchenne Muscular Dystrophy

Abstract: Duchenne muscular dystrophy (DMD) is a severe disorder characterized by progressive muscle wasting,respiratory and cardiac impairments, and premature death. No treatment exists so far, and the identification of active substances to fight DMD is urgently needed. We found that tamoxifen, a drug used to treat estrogen-dependent breast cancer, caused remarkable improvements of muscle force and of diaphragm and cardiac structure in the mdx(5Cv) mouse model of DMD. Oral tamoxifen treatment from 3 weeks of age for 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(93 citation statements)
references
References 89 publications
10
81
1
1
Order By: Relevance
“…In DMD muscle, the fast twitch type II fibers are the first group to break down, while the slow type I fibers remain are the last group to be affected (48). A previous study of skeletal muscle fiber types revealed a greater number of slow, type I fibers in the soleus muscles of Dmd mdx-5Cv mice (49). We tested whether any of the beneficial effects observed in the Dmd mdx-5Cv Tg(Cmk-Mir486) mice might be due to changes in muscle fiber type composition.…”
Section: Figurementioning
confidence: 91%
“…In DMD muscle, the fast twitch type II fibers are the first group to break down, while the slow type I fibers remain are the last group to be affected (48). A previous study of skeletal muscle fiber types revealed a greater number of slow, type I fibers in the soleus muscles of Dmd mdx-5Cv mice (49). We tested whether any of the beneficial effects observed in the Dmd mdx-5Cv Tg(Cmk-Mir486) mice might be due to changes in muscle fiber type composition.…”
Section: Figurementioning
confidence: 91%
“…Additional works also illustrate the benefits of tamoxifen in colorectal cancer [50-52] perhaps demonstrating the need for an in depth evaluation in this area. Other, more recent findings suggest that tamoxifen might be of utility in treating Duchenne muscular dystrophy [53]. Toremifene, a chlorinated derivative of tamoxifen (Fig.…”
Section: Non-sphingolipid-associated Activities Of Tpe’smentioning
confidence: 99%
“…In the absence of dystrophin, the tissue suffers from calcium overload, oxidative stress, and impaired mitochondrial functions, leading to muscle cell death. 35 Any changes in chewing muscles can affect the pattern of masticatory movements and its efficiency. 30 The decrease in masticatory efficiency can lead to improper diet, which, over time, can generate a malnutrition to patients with DMD.…”
Section: R E T R a C T E Dmentioning
confidence: 99%